2015
DOI: 10.1016/j.jmaa.2014.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of quadratic Liénard-type equations by preserving Noether symmetries

Abstract: The classical quantization of a family of a quadratic Liénard-type equation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…Also, we have shown that if we replace the independent variable t with τ = it, then Equation (8) is transformed into Equation (20), which is one of the isochronous Liénard II equations [33]. Its corresponding Schrödinger equation was derived in [23,34]. The eigenfunctions and energy eigenvalues are given in (23) and (24), respectively.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, we have shown that if we replace the independent variable t with τ = it, then Equation (8) is transformed into Equation (20), which is one of the isochronous Liénard II equations [33]. Its corresponding Schrödinger equation was derived in [23,34]. The eigenfunctions and energy eigenvalues are given in (23) and (24), respectively.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…This method was reformulated in [19] for problems that are linearizable by Lie point symmetries, and also successfully applied to various classical problems: second-order Riccati equation [20], dynamics of a charged particle in a uniform magnetic field and a non-isochronous Calogero's goldfish system [18], an equation related to a Calogero's goldfish equation [21], two nonlinear equations somewhat related to the Riemann problem [22], a Liénard I nonlinear oscillator [19], a family of Liénard II nonlinear oscillators [23], N planar rotors and an isochronous Calogero's goldfish system [24], the motion of a free particle and that of a harmonic oscillator on a double cone [25].…”
Section: Quantizing With Noether Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we determine three Lagrangians that admit the highest number of Noether point symmetries with the help of the Jacobi last multiplier [8]. Then, we recall the quantization method that preserves the Noether point symmetries as described for the first time in [19,20], reformulated in [4] for problems that are linearizable by Lie point symmetries (as in the present case), and successfully applied to various classical problems: second-order Riccati equation [21], dynamics of a charged particle in a uniform magnetic field and a non-isochronous Calogero's goldfish system [20], an equation related to a Calogero's goldfish equation [22], two nonlinear equations somewhat related to the Riemann problem [23], a Liénard I nonlinear oscillator [4], a family of Liénard II nonlinear oscillators [5], N planar rotors and an isochronous Calogero's goldfish system [24], a particle on a double cone [6]. Consequently, as a mathematical divertissement, we quantize the second-order differential equation determining the phase-space trajectories of the nonlinear pendulum.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some of these models lead to applications in nano-ribbons [5]. When it comes to the mathematical methods for the symmetries of the nonlinear systems, it is known that any second order non-linear differential equation admits eight parameter Lie point symmetries, thus they are solvable through point transformations [6], [7], [8], [9], [10]. On the other hand, the integrable and super-integrable classical oscillators and their relationships with a nonlinear Liénard type nonlinear equations are given in [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%